Dynamic Magnetic Resonance Angiography Provides Collateral Circulation and Hemodynamic Information in Acute Ischemic Stroke. Issue 2 (February 2016) - Hernández-Pérez, María; Puig, Josep; Blasco, Gerard; Pérez de la Ossa, Natalia; Dorado, Laura; Dávalos, Antoni; Munuera, Josep
Abstract : Background and Purpose—: Contrary to usual static vascular imaging techniques, contrast-enhanced dynamic magnetic resonance angiography (dMRA) enables dynamic study of cerebral vessels. We evaluated dMRA ability to assess arterial occlusion, cerebral hemodynamics, and collateral circulation in acute ischemic stroke. Methods—: Twenty-five acute ischemic stroke patients with proximal anterior circulation occlusion underwent dMRA on a 3T scanner within 12 hours of symptoms onset. Diffusion weighted imaging, T max 6 s lesion volumes and hypoperfusion intensity ratio as volume of T max >6 s/volume of T max >10 s were measured. Site and grade of occlusion (Thrombolysis in Myocardial Infarction criteria) were evaluated on time-of-flight MRA and dMRA. Leptomeningeal collaterality (American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology [ASITN/SIR] Scale) and asymmetries in venous clearance were assessed exclusively on dMRA. Collateral filling was dichotomized into incomplete (ASITN/SIR 0–2) or complete (ASITN/SIR 3–4). Results—: On dMRA, site of occlusion was M1 in 21 patients, tandem internal carotid artery/M1 in 2 and tandem internal carotid artery/terminal internal carotid artery in 2 patients. Three tandem occlusions were not detected on time-of-flight–MRA. All patients had Thrombolysis in Myocardial Infarction 0 to 1 on time-of-flight–MRA, but three of them had Thrombolysis in Myocardial Infarction 2 on dMRA. Complete collateral filling (n=12, 48%) was associated with smaller diffusion weighted imaging lesion volume ( P =0.039), smaller hypoperfused volume ( P =0.018), and lower hypoperfusion intensity ratio ( P =0.006). Patients with symmetrical clearance of transverse sinuses (52%) were more likely to have complete collateral filling ( P =0.015). Conclusions—: As a fast, direct, feasible, noninvasive, and reliable method to assess site of occlusion, collateral circulation and hemodynamic alterations, dMRA provides profound insights in acute stroke. Abstract : Supplemental Digital Content is available in the text.